Systemic RNAi delivery to the muscles of ROSA26 mice reduces lacZ expression. - Jessica Wei; Joel R Chamberlain (PLoS ONE, 2014)
RNAi has potential for therapeutically downregulating the expression of dominantly inherited genes in a variety of human genetic disorders. Here we used the ROSA26 mouse, which constitutively expresses the bacterial lacZ gene in tissues body wide, as a model to test the ability to downregulate gene expression in striated muscles. Recombinant adeno-associated viral vectors (rAAVs) were generated that express short hairpin RNAs (shRNAs) able to target the lacZ mRNA. Systemic delivery of these rAAV6 vectors led to a decrease of β-galactosidase expression of 30-50-fold in the striated muscles of ROSA26 mice. However, high doses of vectors expressing 21 nucleotide shRNA sequences were associated with significant toxicity in both liver and cardiac muscle. This toxicity was reduced in cardiac muscle using lower vector doses. Furthermore, improved knockdown in the absence of toxicity was obtained by using a shorter (19 nucleotide) shRNA guide sequence. These results support the possibility of using rAAV vectors to deliver RNAi sequences systemically to treat dominantly inherited disorders of striated muscle.